Implementasi Sistem Daring (Dalam Jaringan) dan Luring (Luar Jaringan) dalam Pembelajaran Pendidikan Agama Islam - Sherliya Benita; Wirdati Wirdati; Edi Saputra (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to see how the online system and the offline system in PAI learning in schools, especially in class X, because at this time the world of education since the COVID-19 outbreak has experienced changes in the system and implementation of learning that is different from the previous one. This study aims to describe and answer the problem being researched which consists of the principal, two PAI teachers, and 15 students. This research uses a qualitative method with a case study approach. The researcher also uses a purposive sampling data sampling technique, which is a sampling technique where the researcher relies on his own judgment when selecting members of the population to participate in his research. The result of the research is that the implementation of online and offline systems is currently carried out through 3 stages, namely planning, an implementation which includes an opening, core, and closing activities, and the final stage, namely evaluation. The implementation of learning during the Covid-19 pandemic uses a different learning system, namely using online learning applications such as WhatsApp group, zoom, meet and google class.